2010
DOI: 10.1074/jbc.m109.082107
|View full text |Cite
|
Sign up to set email alerts
|

Cul8/Rtt101 Forms a Variety of Protein Complexes That Regulate DNA Damage Response and Transcriptional Silencing

Abstract: The budding yeast, Saccharomyces cerevisiae, has three cullin proteins, which act as platforms for Cullin-based E3 ubiquitin ligases. Genetic evidence indicates that Cul8, together with Mms1, Mms22, and Esc4, is involved in the repair of DNA damage that can occur during DNA replication. Cul8 is thought to form a complex with these proteins, but the composition and the function of Cul8-based E3 ubiquitin ligases remain largely uncharacterized. Herein, we report a comprehensive biochemical analysis of Cul8 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 40 publications
(30 reference statements)
5
67
0
Order By: Relevance
“…Finally, our data strongly suggest that this effect is dependent upon an interaction between Ctf4 and Mms22. Similarly to ctf4D, deletion of MRC1 induces uncoupling between helicase and polymerase (Tanaka et al 2009;Mimura et al 2010;Vaisica et al 2011). In accord with this notion, we found that the replication function of MRC1 is also strongly deleterious for cells experiencing constitutive replicative damages in the absence of a functional H3K56ac pathway.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Finally, our data strongly suggest that this effect is dependent upon an interaction between Ctf4 and Mms22. Similarly to ctf4D, deletion of MRC1 induces uncoupling between helicase and polymerase (Tanaka et al 2009;Mimura et al 2010;Vaisica et al 2011). In accord with this notion, we found that the replication function of MRC1 is also strongly deleterious for cells experiencing constitutive replicative damages in the absence of a functional H3K56ac pathway.…”
supporting
confidence: 76%
“…In the absence of RRM3, chromosome breaks occur at discrete fork pause sites at specific genomic locations (Ivessa et al 2003). A number of studies indicate that the DNA breaks generated in rrm3D cells affect cell viability in the absence of the so-called "H3K56 acetylation pathway" that comprises ASF1, RTT109, RTT101, MMS1, and MMS22 (Tong et al 2004;Luke et al 2006;Pan et al 2006;Collins et al 2007;Duro et al 2008;Roberts et al 2008;Zaidi et al 2008;Costanzo et al 2010;Koh et al 2010;Mimura et al 2010).In S. cerevisiae, H3K56 localizes at the DNA entry and exit points of a nucleosome (Masumoto et al 2005;Ozdemir et al 2005;Xu et al 2005). H3K56 is transiently acetylated during the S phase of the cell cycle and after DNA damage and is rapidly de-acetylated by the action of the sirtuins Hst3 and Hst4, when cells enter the transition between G2 and M phases and after DNA repair (Masumoto et al 2005;Xu et al 2005).…”
mentioning
confidence: 99%
See 3 more Smart Citations